Phenomenon of androgyne as «post-gender»: psychological and philosophical analysis - E. Shishlova (Vestnik MGIMO-Universiteta, 2014)
The article considers psychological aspects of androgynous, dual human nature promoting harmonious relationship among the people, interaction between feminity and masculinity. The concepts of androgyne, androgynity and androgynization which correspond to cultural and socio-political conditions of traditional, modern and post-modern society are introduced. The article examines the history and evolution of the phenomenon of androgyne in ancient mythology, medieval religious philosophy, modern philosophy, present-day psychological science and practice. The author comes to the conclusion that there are two kinds of psychological androgynity: symbolic and real. The real androgynity became the subject of special psychological researches, caused the renunciation of the symbolic one and can be regarded as an important individual feature and human advantage. The transformation of the concept of androgyne is analyzed: from its interpretation as а first man to divine, ritual, psychological androgyne finally regarded as a "post-gender". The results of the study on "Psychological gender in socio-cultural dimension" conducted under the auspices of the Laboratory for Sociological Researches of MGIMO-University (School of International Journalism) are presented.